Strategi Komunikasi Pemasaran Pada Kedai Kopi Kata Kita Bekasi Dalam Meningkatkan Jumlah Pelanggan - Ashari, Alfian; Dharta, Firdaus Yuni; Arindawati, Weni A. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Along with the development of an increasingly rapid lifestyle, especially in big cities such as Bekasi, drinking coffee has become a lifestyle. The purpose of this study was to determine the effect of coffee prices in increasing a sense of comfort or customer loyalty. Qualitative research method is a descriptive research procedure. With a direct approach to the setting and individuals in the overall setting, qualitative research is used to obtain in-depth data, researchers use the constructivism paradigm. Based on the results of research that has been done with interviews and observations made by researchers and analysis of data obtained from the field, literature studies and other sources. The marketing communication strategy carried out by the company is by using a marketing communication strategy in the form of WOM. (Word Of Mouth), advertising (advertising), personal selling (personal selling), and sales promotion (sales promotion). We recommend that Kata Kita Bekasi have a publicity and marketing division in order to better support marketing communication activities carried out through event or marketing activities. it would be nice if this is supported by the use of mass media which has a wider reach